Crystal structure of an HD‐GYP domain cyclic‐di‐GMP phosphodiesterase reveals an enzyme with a novel trinuclear catalytic iron centre. Issue 1 (24th November 2013) - Bellini, Dom; Caly, Delphine L.; McCarthy, Yvonne; Bumann, Mario; An, Shi‐Qi; Dow, J. Maxwell; Ryan, Robert P.; Walsh, Martin A.
Summary Bis‐(3′, 5′) cyclic di‐guanylate (c‐di‐GMP) is a key bacterial second messenger that is implicated in the regulation of many crucial processes that include biofilm formation, motility and virulence. Cellular levels of c‐di‐GMP are controlled through synthesis by GGDEF domain diguanylate cyclases and degradation by two classes of phosphodiesterase with EAL or HD‐GYP domains. Here, we have determined the structure of an enzymatically active HD‐GYP domain protein from Persephonella marina (PmGH) alone, in complex with substrate (c‐di‐GMP) and final reaction product (GMP). The structures reveal a novel trinuclear iron binding site, which is implicated in catalysis and identify residues involved in recognition of c‐di‐GMP. This structure completes the picture of all domains involved in c‐di‐GMP metabolism and reveals that the HD‐GYP family splits into two distinct subgroups containing bi‐ and trinuclear metal centres.